γ-Polyglutamic acid/chitosan nanoparticles for the plant growth regulator gibberellic acid: Characterization and evaluation of biological activity - Pereira, A. E.S. [UNESP]; Sandoval-Herrera, I. E.; Zavala-Betancourt, S. A.; Oliveira, H. C.; Ledezma-Pérez, A. S.; Romero, J.; Fraceto, L. F. [UNESP] (Elsevier, 2017)
The growth regulator gibberellic acid (GA3) has several uses in the field, improving germination, plant development, productivity, and the quality of food. This work describes the development of a nanocarrier system for GA3, based on the poly(γ-glutamic acid) (γ-PGA) and chitosan (CS) polymers, Nanoparticles without GA3 (nano-γPGA/CS-GA3) showed colloidal characteristics, with an average size of 117 ± 9 nm, PDI of 0.43 ± 0.07, and zeta potential of −29 ± 0.5 mV. The encapsulated nanoparticles (nano-γPGA/CS-GA3) presented an average size of 134 ± 9 nm, PDI of 0.35 ± 0.05, zeta potential of 27.9 ± 0.5 mV, and 61% encapsulation. The images of nanoparticles observed by Transmission and scanning electron microscopy (TEM and SEM) showed a spherical shape of the nanoparticles. The system showed sustained release, with 58% release after 48 h. Evaluation of thermal properties using DSC and TGA analyses indicated that there was an interaction between the CS and γ-PGA polymers. In tests using Phaseolus vulgaris seeds, nano-γPGA/CS-GA3 showed high biological activity, enhancing the rate of germination in the first day (50–70%) when compared with free GA3 (10–16%). Encapsulated GA3 was also more efficient than the free hormone in the increase of leaf area and the induction of root development (including the formation of lateral roots). These effects were not observed when seeds were treated with nano-γPGA/CS without GA3. The results demonstrated the considerable potential of nano-γPGA/CS-GA3 for use in agriculture.
Keywords: Agriculture; Chitosan; Gibberellic acid; Nanoparticles; Release system; γ-Polyglutamic acid